Connection Between Technological Trajectory of the Coffee Sector and the Economic Growth of Brazilian Producing Regions - Patricia Turco; Ricardo Firetti; Flavia Bliska; Eder Pinatti; Antonio Bliska; Sergio Tôsto (European Regional Science Association (ERSA), 2014)
This study examines the relationship between the trajectory of technological innovations in Brazilian coffee regions in the period 1932-2012, with the economic growth and development in those areas. The objective of the study is to provide information to public and private institutions involved in research, development, innovation and extension, as well as to the authorities responsible for preparing the regional development policies and for making decisions regarding the application of financial and human resources. First, we studied the evolution of coffee research and identified the technologies that resulted in break points or key points for sectoral development. For this we conducted semi-structured interviews with 14 researchers, farmers and consultants related to the coffee sector. Second, based on the periods in which the breakpoints were identified, we analyzed the trajectories of innovations in each of the five main Brazilian coffee regions. For this, we developed a structured questionnaire, which was applied to 148 representatives of the coffee sector, by random sampling, for the following periods: ? 1932-1954: the beginning of coffee research at the first break point in the sectoral evolution: the release of the first 'modern' coffee cultivar ? 1955 - 1974: the consolidation of the adoption of this cultivar to the second breakpoint in the sectoral evolution: the release of the second 'modern' cultivar and the beginning of mechanized farming; ? 1975 - 1989: consolidation of mechanization and adoption of those two 'modern' cultivars; ? 1990 - 2000: expanding the use of irrigation in crops; ? 2001 - 2012: emphasis on the final product quality and integrated management of production. To analyze the information from the questionnaire, we used cluster analysis by two-way joining method, in which a graph of color scale is generated, which expresses in the vertical reading the technologies used in the analyzed period, and horizontally, the five periods identified in the survey, for Brazil as a whole and for each of the five Brazilian coffee regions. The results show that in regions where technological innovations were adopted and consolidated, there was an increase in productivity and that socioeconomic indicators are significantly better than in other regions.
Keywords: Q16; 330; Coffee production; Regional Development; Multivariate Analysis